Inside: a model for interactive and immersive synchronous media in MOOC courses - Lizzam Abdul Latiff; Azhar Abdul Aziz; Afiza Ismail; Mudiana Mokhsin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
MOOC or Massive Online Open Course is increasingly adopted by Universiti Teknologi MARA as one of the e-learning methods. It is estimated that 900 courses will be offered by end of 2018, in line with the Malaysian Government’s push for better utilization of Information and Communication Technology (ICT) in education. This creates an opportunity to introduce MOOC as a legitimate full alternative to lecture classes. However, learners in a MOOC setting are at a disadvantage when compared to conventional classroom in learner-learner and learner-instructor interaction. There is a huge temporal gap that exists by nature of how the courses are conducted. InSIDE is developed as a model that introduces synchronous interactivity and immersive component within MOOC. To facilitate interaction in this setting, InSIDE suggests a dedicated moderator to accompany the lecture. The model also utilizes a “go high and fail gracefully” approach to overcome the devices, connectivity and infrastructural challenge. In pursuant of the creation of a model that can be used in UiTM, interviews with UiTM’s MOOC facilitators and lecturers were conducted to gain insights on the behind-the-scene processes of creating and managing a course. In order to ensure that the model is feasible within existing infrastructure, a Proof of Concept was conducted with an actual lecture. InSIDE was also presented to three experts on MOOC in UITM. From the qualitative data obtained, 2 out of 3 experts agree that the InSIDE have the possibility to improve MOOC delivery, while one expert agree with reservation in regards required hardware and infrastructure required.